Vismodegib for Advanced Basal Cell Carcinoma Treatment – Experience of 3 Cases - Gameiro, Ana (2016)
Basal cell carcinoma represents the most common skin cancer and its incidence is increasing. Basal cell carcinoma is usually treated surgically or, as an alternative in selected cases, radiation therapy can be used either with curative or adjuvant intention. The designation “advanced basal cell carcinoma” is reserved for cases that cannot be treated by surgery and/or radiotherapy, or when these therapies would imply unacceptable morbidity. “Advanced basal cell carcinoma” includes as well the rare metastatic cases. Vismodegib is the first target drug for advanced basal cell carcinoma, inhibiting the hedgehog signaling pathway. The hedgehog pathway is the etiopathogenic base of Gorlin-Goltz syndrome, and is active in more than 90% of sporadic basal cell carcinoma. Vismodegib shows moderate efficacy rates in advanced BCC, 30% response rate in patients with metastatic basal cell carcinoma, and 43% in locally advanced basal cell carcinoma . We present 3 patients treated with vismodegib, characterizing the clinic evolution and discussing the role of vismodegib for each case. According to our experience, this drug represents a powerful tool for “advanced basal cell carcinoma”, with manageable side effects.